Peran Museum dalam Pembelajaran Sejarah - Dedi Asmara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to find out how the role of the museum in learning history. The method used in this study is qualitative research to understand the phenomenon of what is experienced by research subjects. The results showed that with the shift of the museum paradigm from collection (collection oriented) to visitors (visitor oriented), the wider community had more access to museum collections. The museum must provide various access for visitors so that they can get the opportunity to use facilities and services, research and study collections, display offerings, including consultations with museum staff. The conclusions of this study are that the existence of museums in the world of education is so needed, including in history learning. Both from the low to high education level. A student from elementary school will be happy when studying in a museum, compared to in the classroom. In the museum they can observe ancient relics directly. The learning process can also be carried out by visitors who are not from the education community. A tourist visiting the museum, for him will add to the repertoire of mental and intellectual wealth to know the past from an ethnic or community group. In the museum, collection research can also be carried out, this provides an opportunity to produce the latest findings. Research for students, lecturers, and anyone interested in the museum Keywords: Museums, Learning, Visitors.